2011
DOI: 10.1103/physrevb.83.115319
|View full text |Cite
|
Sign up to set email alerts
|

Carrier recombination dynamics in individual CdSe nanowires

Abstract: Carrier dynamics in single CdSe nanowires (NWs) have been studied using various

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
100
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(107 citation statements)
references
References 44 publications
6
100
1
Order By: Relevance
“…Previous experiments on semiconductor nanowires have typically shown that the fluence dependence of the slow relaxation process is due to Auger recombination. 15,25,27,30 However, as we formerly observed for GaN NW ensembles, 19 we were unable to clearly fit our data with a standard expression for two-or-three carrier Auger recombination. 25,30 This could be due to the fact that we are probing localized defect states and not the extended states that are known to be influenced by Auger recombination, as shown in earlier studies.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…Previous experiments on semiconductor nanowires have typically shown that the fluence dependence of the slow relaxation process is due to Auger recombination. 15,25,27,30 However, as we formerly observed for GaN NW ensembles, 19 we were unable to clearly fit our data with a standard expression for two-or-three carrier Auger recombination. 25,30 This could be due to the fact that we are probing localized defect states and not the extended states that are known to be influenced by Auger recombination, as shown in earlier studies.…”
contrasting
confidence: 56%
“…These issues can be overcome by performing ultrafast optical pump-probe measurements on single NWs, [20][21][22][23][24][25][26][27][28] which has provided much insight into their intrinsic properties. For example, ultrafast optical microscopy (UOM) experiments, which are essentially optical pump-probe experiments with microscopic spatial resolution, have been performed on single Si NWs, revealing the dependence of carrier dynamics on light polarization and excitation fluence 25 as well as the NW diameter.…”
mentioning
confidence: 99%
“…[37,[76][77][78][79][80] Due to the flexibility and ease of employing metal films as catalysts to initiate 1D crystal growth, various groups used chemical vapor deposition (CVD) to synthesize II-VI and III-V semiconductor NWs. [81][82][83][84][85] Despite its versatility, the CVD approach is undesirable for synthesising perovskite NWs due to the low growth temperature of perovskite. Therefore, using the facile solution processable approach to prepare lead halide perovskite is the most appealing approach available to date.…”
Section: D Perovskite: Nanowires and Nanorodsmentioning
confidence: 99%
“…225 This is a well-established approach for characterizing complex, multiprocess recombination dynamics in bulk and nanostructured materials. 34,322,323 Experimental I em versus I exc along with results from the fitting routine are shown in Figure 31B. Individual trapped electron and continuum carrier concentrations at various I exc are displayed in Figure 31C.…”
Section: Recombination Mechanismsmentioning
confidence: 98%